The Long-Awaited Directive on Representative Actions: Still Waiting for Godot… - Nagy, Csongor István (Revista Ítalo-Española de Derecho Procesal, 2020)
On 25 November 2020, the EU adopted the Directive on Representative Actions. This long-awaited legal instrument is the first to create a binding European-wide collective action mechanism for monetary relief. Notwithstanding that it was supposed to crown three decades of intellectual efforts, the Directive failed to establish a workable system going beyond traditionalist fundamentalism. The Directive takes a markedly minimalist approach and its only added value is that some collective mechanism, however ineffective and low-key, should be available in every Member State. This paper provides an analytical overview of the Directive in light of the pertinent European debate. Section 2 provides a general presentation and assessment of the Directive’s scope and nature and the issues it fails to address. The rest of the sections deals with the Directive’s different regulatory chapters. Section 3 deals with the rules on standing and qualified entities. Section 4 addresses the Directive’s provisions on opt-in and opt-out. Section 5 presents the safeguards the Directive sets up against abusive litigation. Section 6 contains the paper’s conclusions and defines the incremental value generated by the Directive (it takes stock of those elements that may represent an added value in comparison to the pre-Directive regulatory situation).